Polynomial Powerpoint

16,005 views

Published on

Published in: Technology, Spiritual
0 Comments
0 Likes
Statistics
Notes
  • Be the first to comment

  • Be the first to like this

No Downloads
Views
Total views
16,005
On SlideShare
0
From Embeds
0
Number of Embeds
2,947
Actions
Shares
0
Downloads
277
Comments
0
Likes
0
Embeds 0
No embeds

No notes for slide

Polynomial Powerpoint

  1. 1. (3x2 + 5x + 3) + (2x2 – 3x + 1)<br />
  2. 2. (3x2+ 5x + 3) + (2x2 – 3x + 1)<br />
  3. 3. (3x2+ 5x + 3) + (2x2– 3x + 1)<br />
  4. 4. (3x2+ 5x+ 3) + (2x2– 3x + 1)<br />
  5. 5. (3x2+ 5x+ 3) + (2x2– 3x + 1)<br />
  6. 6. (3x2+ 5x+ 3) + (2x2– 3x + 1)3x2 + 2x2= <br />
  7. 7. (3x2+ 5x+ 3) + (2x2– 3x + 1)3x2 + 2x2= 5x2<br />
  8. 8. (3x2+ 5x+ 3) + (2x2– 3x + 1) 3x2 + 2x2= 5x25x – 3x = <br />
  9. 9. (3x2+ 5x+ 3) + (2x2– 3x + 1) 3x2 + 2x2= 5x25x – 3x = 2x<br />
  10. 10. (3x2+ 5x+ 3) + (2x2– 3x + 1)3x2 + 2x2= 5x25x – 3x = 2x3 + 1 = <br />
  11. 11. (3x2+ 5x+ 3) + (2x2– 3x + 1)3x2 + 2x2= 5x25x – 3x = 2x3 + 1 = 4<br />
  12. 12. (3x2+ 5x+ 3) + (2x2– 3x + 1)3x2 + 2x2= 5x25x – 3x = 2x3 + 1 = 4<br />5x2+ 2x + 4<br />
  13. 13. (6x – 4y + 2z) – (2x + 7y – 4z) <br />
  14. 14. (6x – 4y + 2z) – (2x + 7y – 4z) <br />
  15. 15. (6x – 4y + 2z) – (2x + 7y – 4z) <br />
  16. 16. (6x – 4y + 2z) – (2x + 7y – 4z) <br />
  17. 17. (6x – 4y + 2z) – (2x + 7y – 4z) <br />
  18. 18. (6x – 4y + 2z) – (2x + 7y – 4z) <br />
  19. 19. (6x– 4y + 2z) – (2x+ 7y – 4z) <br />
  20. 20. (6x– 4y + 2z) – (2x+ 7y – 4z) <br />
  21. 21. (6x– 4y + 2z) – (2x+ 7y – 4z) <br />
  22. 22. (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = <br />
  23. 23. (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = 4x<br />
  24. 24. (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = 4x-4y + -7y = <br />
  25. 25. (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = 4x-4y + -7y = -11y<br />
  26. 26. (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = 4x-4y + -7y = -11x2z + 4z =<br />
  27. 27. (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = 4x-4y + -7y = -11x2z + 4z = 6x<br />
  28. 28. (6x– 4y + 2z) – (2x+ 7y – 4z) 6x + -2x = 4x-4y + -7y = -11x2z + 4z = 6z<br />4x– 11y + 6z<br />
  29. 29. AlgeBlocks<br />y<br />x2<br />x<br />1<br />y<br />x2<br />x<br />1<br />
  30. 30. (2x2 + 3x + 1) + (x2 + 2x + 4)<br />
  31. 31. (2x2 + 3x + 1) + (x2 + 2x + 4)<br />x2<br />x2<br />x2<br />x<br />x<br />x<br />x<br />x<br />1<br />1<br />1<br />1<br />1<br />
  32. 32. 3x2 + 4x + 5 <br />x2<br />x2<br />x2<br />x<br />x<br />x<br />x<br />1<br />1<br />1<br />1<br />1<br />
  33. 33. (5x – 4y ) + (2x + y)<br />
  34. 34. (5x – 4y ) + (2x + y)<br />x<br />x<br />x<br />x<br />x<br />x<br />x<br />y<br />y<br />y<br />y<br />y<br />
  35. 35. x<br />x<br />x<br />x<br />x<br />x<br />x<br />y<br />y<br />y<br />y<br />y<br />
  36. 36. x<br />x<br />x<br />x<br />x<br />x<br />x<br />y<br />y<br />y<br />y<br />y<br />
  37. 37. x<br />x<br />x<br />x<br />x<br />x<br />x<br />y<br />y<br />y<br />
  38. 38. 7x – 3y <br />x<br />x<br />x<br />x<br />x<br />x<br />x<br />y<br />y<br />y<br />
  39. 39. (x2 – 3x + 2) – (4x2 + x – 4) <br />
  40. 40. (x2 – 3x + 2) – (4x2 + x – 4) <br />
  41. 41. (x2 – 3x + 2) – (4x2 + x – 4) <br />
  42. 42. (x2 – 3x + 2) – (4x2 + x – 4) <br />x2<br />x2<br />x2<br />x2<br />x2<br />x<br />x<br />x<br />x<br />1<br />1<br />1<br />1<br />1<br />1<br />
  43. 43. x2<br />x2<br />x2<br />x2<br />x2<br />x<br />x<br />x<br />x<br />1<br />1<br />1<br />1<br />1<br />1<br />
  44. 44. x2<br />x2<br />x2<br />x2<br />x2<br />x<br />x<br />x<br />x<br />1<br />1<br />1<br />1<br />1<br />1<br />
  45. 45. x2<br />x2<br />x2<br />x<br />x<br />x<br />x<br />1<br />1<br />1<br />1<br />1<br />1<br />
  46. 46. -3x2 – 4x + 6 <br />x2<br />x2<br />x2<br />x<br />x<br />x<br />x<br />1<br />1<br />1<br />1<br />1<br />1<br />

×